Slip distribution beneath the Central and Western Himalaya inferred from GPS observations - Ponraj, M.; Miura, S.; Reddy, C. D.; Amirtharaj, S.; Mahajan, S. H. (My University, 2011)
Underthrusting of the Indian Plate beneath the Himalaya has been the cause of many hazardous thrust-faulting earthquakes along the arc. Moderate earthquakes with magnitudes of ≤5 occur frequently in this region, releasing the elastic strain accumulated over many years around the plate boundary. These events can be attributed to slip deficits where the Indian and Eurasian Plates are locked during interseismic periods. Geodetic measurements can help discriminate the distribution of the interlocking areas and the steadily slipping areas beneath the Himalaya. To understand the deformation across the Central and Western Himalaya and the associated slip on thrust faults, campaign-mode GPS data were collected in the Garhwal–Kumaun region of the Western Himalaya. GPS sites velocities show that the deformation is currently concentrated between the Lesser and Higher Himalaya. Horizontal velocities are used to estimate the slip distribution. For the estimation, a model of the interseismic surface deformation caused by buried non-uniform creep dislocation (NUC) on a curved fault surface is used. The slip distribution shows that there might be structural discontinuity on the fault between the Kumaun and Garhwal regions of the Himalaya. The estimated slip rate at the depth around 20–40 km in the Central Himalaya and at the depth of ∼15 km in the Western Himalaya is 10 mm yr–1. The NUC model indicates that the shallow part (<20 km) of the thrust fault system along the plate boundary is almost locked. The locking depth appears to be deep in the Central Himalaya and shallower in the Western Himalaya. Further, most of the historical large seismic events are observed to have occurred in an area with a slip velocity less than 10 mm yr–1 (i.e. in a locked zone) at the plate interface.
Keywords: Satellite geodesy; Creep and deformation; Seismicity and tectonics; GPS observations